RELATIONSHIP BETWEEN OPERATOR KNOWLEDGE AND HYGIENE WITH BACTERIOLOGICAL QUALITY OF REFILL DRINKING WATER IN BANYUWANGI, INDONESIA: A CROSS-SECTIONAL STUDY - Ramadhan, Syahrul; Adriyani, Retno; Larasati, Adella Atika; Husaini, Ahmad; Sham, Shaharuddin bin Mohd (Journal of Public Health Research and Community Health Development, 2024)
Background: Refill Drinking Water (AMIU) is one of the alternatives used by the Indonesian people in meeting their drinking water needs. However, there are still AMIUs that do not meet the total coliform standard. Purpose: This study aimed to analyze the relationship between DAMIU operators' knowledge and hygiene measures on the bacteriological quality of AMIU in Banyuwangi Sub-district, Banyuwangi, East Java Province, Indonesia. Methods: This was an observational study with a cross-sectional approach. Water samples from 33 DAMIUs in Banyuwangi sub-district were tested for total coliforms. DAMIU operators were interviewed using a structured questionnaire regarding knowledge and hygiene. Data were analyzed using Chi-square test. Results: Twelve out of 33 (36.4%) AMIUs did not meet the total coliform standard. Thirty-one (93.9%) DAMIU operators had excellent knowledge, and 23 (69.7%) had good personal hygiene. There was a significant association between operator hygiene and total coliform quality of AMIU (p=0.016; OR=8.4). Conclusion: Operator hygiene is an important factor in meeting the bacteriological quality standards of AMIU. It is recommended to make efforts to raise awareness of DAMIU operators to always apply hygiene while working.